Application of multiplex methylated‐specific PCR with capillary electrophoresis to explore prognostic value of TSGs hypermethylation for hepatocellular carcinoma. Issue 6 (7th March 2018) - Huang, Yuan; Wei, Ling; Sun, Ai‐min; Li, Bo; Sun, Cheng‐jun; Liang, Wei‐bo; Liu, Qiu‐ying; Yu, Xiao‐qin; He, Jing‐yang; Qin, Yang
Abstract : Background: Hepatocellular carcinoma (HCC) is a malignant tumor that severely threatens human health. To date, early detection for HCC patients is particularly significant due to their poor survival rates even after liver resection. Methods: Therefore, an efficient and sensitive detection method for monitoring liver cancer, multiplex methylation‐specific PCR (MSP) coupled with capillary electrophoresis, is developed. Results: Simulations demonstrated that the methylation status of RASSF1A, p16, SFRP1, and ELF could be detected even when DNA equaled or exceeded 12.5 ng simultaneously. Also, its accuracy for methylation detection outweighed polyacrylamide gel electrophoresis (87.5%) and agarose electrophoresis (84.3%), reaching 92.1%. Subsequently, we implemented multiplex MSP with capillary electrophoresis to investigate methylation status of the four tumor suppressor genes in tissue specimens and explore the prognostic value for HCC patients. As the data suggested, multivariate cox regression analysis revealed that the recurrence‐free survival of 46 patients was greatly associated with portal vein tumor thrombus (PVTT) and p16 methylation and receiver operating characteristic (ROC) curves demonstrated that the predictive range of portal vein tumor thrombus (PVTT) combined with p16 hypermethylation was more sensitive than that of either PVTT or p16 hypermethylation alone with regard to disease recurrence in patients with HCC, which could be testified as a valuable biomarker in Clinical application. Conclusion: Multiplex MSP coupled with capillary electrophoresis has an excellent prospect of clinical application for monitoring early liver cancer and screening valuable biomarkers for prognosis of HCC patients.